Insulin vs GLP-1 analogues in poorly controlled Type 2 diabetic subjects on oral therapy: A meta-analysis - Abdul-Ghani, Muhammed; Williams, Ken; Kanat, Mustafa; Altuntaş, Yüksel; DeFronzo, Ralph Albarado (Editrice Kurtis S R L, 2013)
To compare insulin and GLP-1 analogues therapy on glycemic control in poorly controlled Type 2 diabetes (T2DM) subjects failing on oral therapy. Methods: The electronic database PubMed was systematically searched for randomized controlled trial (RCT) with duration >16 weeks comparing the addition of insulin therapy vs glucagon-like peptide (GLP-1) analogues in poorly controlled T2DM subjects on oral therapy. Results: We identified 7 RCT with 2199 patients of whom 1119 were assigned to insulin therapy and 1080 received a GLP-1 analogue. Both insulin and GLP-1 analogues were effective in lowering glycated hemoglobin (HbA(1c)) with no statistically significant difference between the mean decreases in HbA(1c). However, insulin was more effective than GLP-1 analogues in lowering the fasting plasma glucose concentration, while GLP-1 agonists were more effective in lowering the postprandial glucose concentration. Insulin therapy was associated with weight gain while GLP-1 analogues consistently caused weight loss and the difference between the mean change in body weight between the two therapies was highly statistically significant. Despite a similar decrease in HbA(1c), the risk of hypoglycemia was 35% lower (p=0.001) with GLP-1 therapy compared to insulin. Compared to insulin, GLP-1 analogues caused a significant decrease in systolic blood pressure and were associated with greater rate of gastrointestinal adverse events. Conclusion/interpretation: In poorly controlled T2DM subjects on oral therapy, GLP-1 analogues and insulin are equally effective in lowering the HbA(1c). However, GLP-1 analogues have additional non-glycemic benefits and lower risk of hypoglycemia. Thus, GLP-1 analogues should be considered as a treatment option in this group of diabetic individuals.
WOS: 000319889300005
PubMed ID: 22522662
Keywords: GLP-1 analogues; Insulin; Meta-Analysis; Type 2 diabetes